Analysis of C-Peptide Levels Among Gynaecological Malignancies Patients Underwent Chemotherapy with Carboplatin Regiment - Nina Tristina; Juandika Juandika; Leni Lismayanti; Adhi Kristianto Sugianli; Raja Iqbal Mulya Harahap (Indonesian Association of Clinical Pathologist and Medical laboratory, 2022)
C-peptide is part of the, which its amounts were equal to endogenous insulin secreted by pancreatic Î² cells. Carboplatin is one of the chemotherapy regimens that are widely used to treat gynecological malignancies. Carboplatin may cause the damage of Î²-islets of Langerhans, which may cause defects in insulin synthesis leading to secondary diabetes mellitus or other types of diabetes mellitus. The purpose of this study was to determine the differences in C-peptide, (which reflects endogenous insulin levels) levels in patients with gynecologic malignancy who underwent carboplatin chemotherapy. This study was a comparative observational study with a cross-sectional design. There was a total of 42 subjects who met the inclusion criteria. Subjects with gynecological malignancy post-carboplatin chemotherapy regimens had lower serum C-peptide levels in group II compared to group I. Serum C-peptide levels can further be used to monitor side effects of carboplatin and can be used as a test to diagnose the other types of diabetes mellitus especially before starting the fourth cycle